Enhancing Accessibility to Islamic Studies Education through E-learning - Issa, Usman Adisa; Jibril, Ayuba Olaniyi; Abdulrazaq, Abdulraheem (Indonesian Journal of Educational Research and Review, 2023)
The E-learning system of education allows students to acquire uninterrupted learning activities through the aids of technological devices. E-learning as a process of receiving knowledge through electronic transmission, can be an alternative teaching and learning method. Therefore, this study analyzes e-learning: a conducive avenue for making learning more accessible among senior secondary school Islamic studies. This type of research is qualitative research. The data collection method is including, interviews and FGDs. Then data analysis uses qualitative analysis. The finding of the study revealed that the integration of e-learning enhances the effective and efficient learning process. Also, the study revealed that students with very low enthusiasm for learning may find it difficult to utilize e-learning and the unfriendly nature of the internet in Nigeria discourages students from adopting it. It is, therefore, concluded in this study that e-learning is an alternative medium for achieving educational objectives and a reliable means to enhance effective and efficient teaching and learning processes in this 21st century.